ASSESSMENT OF FOLATE STATUS: MEASUREMENT OF HOMOCYSTEINE versus VITAMIN B12 AND FOLATE (Sciences & Technologie. C, Biotechnologies, 2004)
There was no statistically significant difference between controls and patients for dietary folate. Also the plasma folate level did not slightly differ between the controls and patients. Patients had higher average homocysteine concentrations than control subjects (p